Microbioma in Aging Skin - Nugraheni Pasaribu, Uly Aanda Maria; Rihatmadja, Rahadi; Yusharyahya, Shannaz Nadia; Widaty, Sandra; Legiawati, Lili; Pandjaitan-Sirait, Sondang MHA (Newinera Publisher, 2024)
Microbiota is inseparable to the skin. Just as in the gastrointestinal tract, the skin microbiome reflects the health of the organ where it resides. It contributes to skin barrier function and ensures its homeostasis. However relatively stable over time, microbiome composition and number may be influenced by various aging -related changes − dryness, blemish, wrinkles and alteration of sebaceous gland activity impacting the skin ecological conditions − and vice versa. Several generations have been reported to promote the process while others may play a more protective role in this regard.